The Conditioned Medium of Calcined Tooth Powder Promotes the Osteogenic and Odontogenic Differentiation of Human Dental Pulp Stem Cells via MAPK Signaling Pathways - Jintao Wu; Na Li; Yuan Fan; Yanqiu Wang; Yongchun Gu; Zehan Li; Yin Pan; Gobin Romila; Zuomin Zhou; Jinhua Yu (Stem Cells International)
The calcined tooth powder (CTP), a type of allogeneic biomimetic mineralized material, has been confirmed that can promote new bone formation when obtained at high temperature. The aim of this study was to investigate effects of the conditioned medium of calcined tooth powder (CTP-CM) on the osteogenic and odontogenic differentiation of human dental pulp stem cells (hDPSCs) and the underlying mechanisms involved. First, ALP activity assay determined that 200 μg/mL was the optimal concentration of CTP-CM for the following experiments. CTP-CM had no significant effect on the proliferation of hDPSCs as indicated by CCK-8 and FCM analysis. Both the gene and protein (DSPP/DSPP, RUNX2/RUNX2, OCN/OCN, OSX/OSX, OPN/OPN, ALP/ALP, and COL-1/COL-1) expression levels increased in the CTP-CM-induced hDPSC group as compared with those in the control group at day 3 or 7, showing the positive regulation of CTP-CM on the osteo/odontogenic differentiation of hDPSCs. Mechanistically, MAPK signaling pathways were activated after the CTP-CM treatment, and the inhibitors targeting MAPK were identified which weakened the effects of CTM-CM on the committed differentiation of hDPSCs. These findings could lead to the creation of stem cell therapies for dental regeneration.